Perencanaan Pajak dan Manajemen Laba: Peran Komisaris Independen pada Bank Konvensional - Ferninda Dewi Ayu; Nurul Aisyah Rachmawati (Juara: Jurnal Riset Akuntansi, 2026)
One of the crucial elements in the implementation of Good Corporate Governance (GCG) in the banking sector is the financial and tax management that are carried out transparently and efficiently. This study explores how tax planning relates to earnings management practices in conventional banks across Indonesia, highlighting the important role that independent commissioners play as a moderating factor. A quantitative approach is used, with logistic regression, to explore how tax planning influences the likelihood of earnings management and to assess the contribution of independent commissioners in moderating this relationship. The financial statements of conventional banks listed on the Indonesia Stock Exchange from 2021 to 2024 were used to gather data, and the samples were chosen carefully through purposive sampling. Data analysis was conducted utilizing STATA software. The findings suggest that tax planning doesn't have a big impact on earnings management, and the presence of independent commissioners doesn't seem to make a significant difference either. This finding implies that highly regulated environments, particularly in the banking sector, may restrict firms’ ability to undertake tax planning, making its influence on earnings management less evident.